High quality hybrid perovskite semiconductor thin films with remarkably enhanced luminescence and defect suppression via quaternary alkyl ammonium salt based treatment - Naphade, Rounak A.; Zhao, Baodan; Richter, Johannes M.; Booker, Edward; Krishnamurthy, Shrreya; Friend, Richard H.; Sadhanala, Aditya; Ogale, Satishchandra B. (Advanced Materials Interfaces, 2017)
Significant enhancement in the luminescence and superior photophysical properties of CH3NH3PbBr3 thin films prepared via simple single step spin coating process involving a novel additive mediated solvent extraction step is reported. This process results in significantly lower disorder in CH3NH3PbBr3 perovskites with Urbach energies reducing from ≈35 to ≈17 meV, which is the lowest reported value to date. The additive mediated process also results in a remarkable improvement in the photoluminescence quantum yields (PLQYs) from 1% to 30%. Coupled with the overall increase in surface roughness, a significant increase in the internal PLQY from 7% to 77% is estimated, indicating the superior quality of the treated thin films. The resultant high quality CH3NH3PbBr3 perovskites with remarkable photophysical properties can be used in realizing highly efficient optoelectronic devices. Highly efficient light emitting diodes using these perovskites are demonstrated here.

Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells